Happy Dentition-Homoeopathic Care Management for Teething Infants (Homoeopathy for All, 2024)
The time of teething varies from  child to child, but it usually starts  from 6 months to 12 months of age.  Teething is the process by which  an infant’s teeth erupt, or break  through, the gums. Teething is also  referred to as “cutting” of the teeth.  Homoeopathy has been found to be  very successful in treating dentition  problems in children’s and medicines  are perfectly safe. A homoeopathic  teething remedy includes medicines  that ease the symptoms like  irritability and swelling in teething  toddlers. Homoeopathic medicines  also helps baby calm down and get  to sleep.
Keywords: Dentition; Management; Infants